EFISIENSI LAPANG ALAT TANAM BENIH LANGSUNG (TABELA) PADI SAWAH DENGAN MENGGUNAKAN TRAKTOR TANGAN SEBAGAI TENAGA TARIK - Feryatmono O. Geso; Ruland Rantung; Daniel P M. Ludong (COCOS, 2018)
ABSTRACTThis study aimed to calaulete the field efficiency of direct seed planting equipment (Tabela) using a hand tractor as a pulling tool. The field evaluation was conducted on an area of 120 m2 that was divided into 3 plots. In this study the distance between planting rows was 20 cm, the legowo rows distance was 40 cm the average of planting depth was 1,4 cm, the the seed number each hole was 3-7 seeds and the average was 4 seeds. The results showed that the field efficiency was 53,53 %. This direct seed planting equipment reduced the number of labors and working time. Â Keywords : Tabela tool, Hand Tractor, Legowo